2010
DOI: 10.1002/mus.21765
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of the motor unit number index (MUNIX) in normal controls and amyotrophic lateral sclerosis patients

Abstract: The motor unit number index (MUNIX) refers to an electrophysiologic technique that measures the approximate number of motor units using the surface electromyographic interference pattern (SIP) recorded during voluntary contraction. This study was done to assess the reproducibility of MUNIX performed on hypothenar muscles in 62 normal controls and 22 amyotrophic lateral sclerosis (ALS) patients. Inter- and intraoperator correlation coefficients for MUNIX were 0.74 and 0.86, respectively, in normal controls, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
91
4
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 82 publications
(117 citation statements)
references
References 19 publications
19
91
4
3
Order By: Relevance
“…2,3 In conclusion, the mean values of MUNIX, the inter-operator COV (APB; 14.3, ADM; 13.6, Table 1), and the correlation coefficients (0.849 and 0.807, Table 1) indicate that the measurements after applying the digital dynamometer were much more reliable compared to those obtained in previous MUNIX and MUNE investigations. 2,3,[5][6][7][8][9][10][11] This technical improvement can be attributed to our efforts to reduce the test-retest variability while recording SIP signals by assuring close monitory through the digital dynamometer. In addition, our study revealed excellent test-retest reproducibility of MUSIX when assessing the average size of the motor units by using the digital instrument.…”
Section: -6mentioning
confidence: 51%
See 4 more Smart Citations
“…2,3 In conclusion, the mean values of MUNIX, the inter-operator COV (APB; 14.3, ADM; 13.6, Table 1), and the correlation coefficients (0.849 and 0.807, Table 1) indicate that the measurements after applying the digital dynamometer were much more reliable compared to those obtained in previous MUNIX and MUNE investigations. 2,3,[5][6][7][8][9][10][11] This technical improvement can be attributed to our efforts to reduce the test-retest variability while recording SIP signals by assuring close monitory through the digital dynamometer. In addition, our study revealed excellent test-retest reproducibility of MUSIX when assessing the average size of the motor units by using the digital instrument.…”
Section: -6mentioning
confidence: 51%
“…The MUNIX method involved assessing the APB and ADM muscles and the compound muscle action potential (CMAP) of the APB and ADM muscles were recorded using 10-mm flat disk electrodes with standard nerve conduction protocols stimulating median and ulnar nerve supramaximally, as has been previously reported. [1][2][3][4][5] The ADM and APB muscles were fully activated respectively by abduction of the little finger or by abduction of the thumb against a digital instrument calibrated by the manufacturer (Jamar Plus ® + Digital Hand Dynamometer, Sammons Preston Inc., Bolingbrook, IL, USA), and thereby the maximal muscle power could be digitally checked. Each muscle was gradually re-activated at five different levels of isometric force from minimum to maximum (slight, 25%, 50%, 75%, and 100%) using a digital instrument.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations